3D culture technologies of cancer stem cells: promising ex vivo tumor models. (June 2020) - Zhang, Chengye; Yang, Zhaoting; Dong, Da-Long; Jang, Tae-Su; Knowles, Jonathan C.; Kim, Hae-Won; Jin, Guang-Zhen; Xuan, Yanhua
Cancer stem cells have been shown to be important in tumorigenesis processes, such as tumor growth, metastasis, and recurrence. As such, many three-dimensional models have been developed to establish an ex vivo microenvironment that cancer stem cells experience under in vivo conditions. Cancer stem cells propagating in three-dimensional culture systems show physiologically related signaling pathway profiles, gene expression, cell–matrix and cell–cell interactions, and drug resistance that reflect at least some of the tumor properties seen in vivo . Herein, we discussed the presently available Cancer stem cell three-dimensional culture models that use biomaterials and engineering tools and the biological implications of these models compared to the conventional ones.